Deletion of GSTM1 and GSTT1 Genes and Lung Cancer Survival: a Systematic Review. Issue 4 (July 2017) - Hernández, Cristina Ramos; Mouronte-Roibás, Cecilia; Barros-Dios, Juan Miguel; Fernández-Villar, Alberto; Ruano-Ravina, Alberto
Purpose: The mechanisms of lung carcinogenesis are not fully understood. Not all smokers develop lung cancer, indicating that genetic variations and other environmental factors may play an important role in its development. The human glutathione S-transferases (GSTs) have been associated with an increased risk of lung cancer. Glutathione S-transferases are phase II biotransformation enzymes that play a role in detoxifying a wide range of exogenous agents including carcinogens but also anticarcinogenic drugs. Methods: We assessed the effect of allelic deletions in the GSTM1 and GSTT1 genotypes on lung cancer overall survival through a systematic review of the scientific literature after applying predefined inclusion and exclusion criteria. Results: Most of the included studies found no effect or a tendency to worse survival for individuals with deletion of GSTs. Conclusions: Further studies are necessary to understand the magnitude of the effect of the deletion of both genes on lung cancer survival.